2005
DOI: 10.1128/aem.71.6.2999-3006.2005
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus parasiticus Cyclase Catalyzes Two Dehydration Steps in Aflatoxin Biosynthesis

Abstract: In the aflatoxin biosynthetic pathway, 5-oxoaverantin (OAVN) cyclase, the cytosolic enzyme, catalyzes the reaction from OAVN to (2S,5S)-averufin (AVR) (E. Sakuno, K. Yabe, and H. Nakajima, Appl. Environ. Microbiol. 69:6418-6426, 2003). Interestingly, the N-terminal 25-amino-acid sequence of OAVN cyclase completely matched an internal sequence of the versiconal (VHOH) cyclase that was deduced from its gene (vbs). The purified OAVN cyclase also catalyzed the reaction from VHOH to versicolorin B (VB). In a compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…-aflK (vbs) was firstly associated with the conversion of versiconal into versicolorin B but was also reported to be responsible for the transformation of OAVN into AVF [47]. Indeed, when Sakuno et al [47] elucidated the intermediate metabolite between HAVN and AVF, the 5 -oxoaverantin (OAVN), this transformation was also associated with the aflK gene. These authors were the first to demonstrate that the same enzyme can catalyze two different reactions in the AFB1 pathway.…”
Section: Conversion Of Norsolorinic Acid Into Versicolorin Amentioning
confidence: 99%
“…-aflK (vbs) was firstly associated with the conversion of versiconal into versicolorin B but was also reported to be responsible for the transformation of OAVN into AVF [47]. Indeed, when Sakuno et al [47] elucidated the intermediate metabolite between HAVN and AVF, the 5 -oxoaverantin (OAVN), this transformation was also associated with the aflK gene. These authors were the first to demonstrate that the same enzyme can catalyze two different reactions in the AFB1 pathway.…”
Section: Conversion Of Norsolorinic Acid Into Versicolorin Amentioning
confidence: 99%
“…15) Further, this compound was converted into AVR by OAVN cyclase prepared from A. parasiticus NIAH 26. 15,16) Since OAVN was so unstable that it was easily converted to AVR by acid treatment or dryness, we supposed for a long time that AVR was the product of this enzyme reaction. We confirmed that Lac-HAVN dehydrogenase had the same activity for conversion of HAVN to OAVN as A. parasiticus HAVN dehydrogenase did.…”
Section: Conversion Of Havn To Oavnmentioning
confidence: 99%
“…1). 15,16) Since OAVN is an unstable substance, it easily changes to AVR by spontaneous dehydration. Chang et al have reported a DNA sequence encoding the HAVN dehydrogenase of A. parasiticus and confirmed its function by gene disruption.…”
mentioning
confidence: 99%
“…All of these known compounds (2)(3)(4)(5)(6) were involved in the aflatoxin biosynthetic pathway of Aspergillus spp. [12,13]; hence, the co-occurring compound 1 could be presumed to be biosynthesized by the same pathway.…”
mentioning
confidence: 99%
“…MHz, DMSO-d6 ) and13 C NMR (150 MHz, DMSO-d 6 ), see Table 1. ESI-MS m/z 397.1 [M -H] -; HR-ESI-MS m/z 397.0922 (calcd for C 21 H 17 O 8 , 397.0918).…”
mentioning
confidence: 99%